Liberalization, Prudential Supervision, and Capital Requirements : The Policy Trade-Offs - Ribakova, Elina (IMF Working Papers; Working Paper ;, 2005)
While deregulated financial markets and strong competition are commonly viewed as prerequisites for successful economic development, recent empirical evidence suggests that financial liberalization, if not well phased, can lead to costly financial crises. This paper focuses on the roles of minimum capital requirements and prudential supervision in promoting financial stability during financial liberalization. The paper extends the Hellmann, Murdock, and Stiglitz model to analyze the effects of prudential supervision and demonstrates the trade-off between the quality of supervision and the level of minimum capital requirements. Where prudential supervision is poor, higher capital requirements are optimal.